Study for the Necropolis of Deneia with the use of satellite images - Georgiades, Ioannis (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This study aims at the processing of satellite images for purposes that help the field of archeology. The use of satellite images is relatively new in the field of archeology and therefore their usefulness is constantly being discussed. For the needs of this study, the prehistoric settlement of Denia was chosen in the Early Copper Age (2500-2075 BC), where an extensive cemetery was found of great importance for the history of Cyprus. For the purpose of the study, satellite images of the Sentinel 2 satellite were used and with the help of the SNAP software they were processed to investigate whether the graves found in this area can be easily identified. The first processing method used in satellite imagery was the application of a high pass filter in the B8 band. Laplace filter was then used for better results, and one of the most well-known vegetation indices, the NDVI was used. The results after the processing of satellite images based on the above methods show that the particular satellite combined with the small size of the tombs did not help sufficiently to obtain satisfactory results. In conclusion, Cyprus in the field of archeology needs great progress in the development of the use of satellite images and, more generally, in the field of remote sensing for easier identification of possible archaeological sites and the possibility of monitoring the situation in the occupied part of the island.
Keywords: Satellites; Images; Process; Remote sensing; Tombs; Δορυφόροι; Εικόνες; Επεξεργασία; Τηλεανίχνευση; Τάφοι